Employee Training. Employee Empowerment, Internal Communication, Employee Motivation And Service Quality At Bank X - Rahmawati, Annisa; Witjaksono, Beny; Ramli, Abdul Haeba (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The importance of providing service value to customers is recognized as a crucial strategy for achieving success in today's fierce competition. Perceived service value is an important factor in service marketing strategy and a key element in customer decision making. This study aims to examine the effect of training and employee empowerment on perceived service quality and the mediating role of employee motivation and internal communication on the relationship between employee empowerment and service quality. This research is quantitative with purposive sampling technique, using questionnaires distributed to 125 employee respondents in the JABODETABEK banking industry. Data analysis was conducted using the Structural Equation Modeling (SEM) method with a sample of bank employees in the service sector such as Teller and Customer Service who have worked for at least one year. The results showed that 10 hypotheses were accepted, and the employee training variable had the greatest direct effect on employee empowerment. Then employee empowerment has the greatest indirect effect on employee training and perceived service quality. This study contributes to banks to achieve more optimal service performance and build closer relationships with customers which in turn will add value to bank performance and suggests future researchers to expand the scope of the study by involving several banks or other financial institutions to increase the generalizability of the findings. Keywords: Employee Training. Employee Empowerment, Internal Communication, Employee Motivation, Perceived Service Quality